Construction of the gripper with strength control in real-time - Piotrowiak, Arkadiusz; Ciszak, Olaf; Mroczyk, Marcin; Jacków, Mikołaj (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2016)
In paper was presented the concept and design of the gripper control holding force in real time. It describes in detail the various stages of the design process. It brought closer the process of execution and describes the problems encountered with their solution. It also presents the principle and algorithm of actions designed gripper. There were also presented operating characteristics of the device working as an industrial robot gripper. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)